GAP ANALYSIS AND ENHANCEMENT STRATEGY FOR SUPPLY CHAIN PERFORMANCE IN THE HANDICRAFT INDUSTRY OF ISR BONE SMES: A SCOR RACETRACK APPROACH - Fole, Asrul; Immawan, Taufik; Kusrini, Elisa; Mail, Abdul; Dahlan, Muhammad (Journal of Industrial Engineering Management, 2024)
Supply chain performance is a crucial factor for the handicraft industry in coping with the increasing and complex competition. This study aims to determine the enhancement strategy for the supply chain performance in the handicraft industry of ISR Bone SMEs in the Reliability sector by using the SCOR Racetrack version 12.0 method. This method can assess the gap between actual and target performance on level 1 and level 3 metrics. The results of the study indicate that there is a significant gap in the RL.1.1 Perfect Order Fulfillment metric of 78.63% and in the level 3 metrics: RL.3.32, RL.3.24, and RL.3.55. The proposed enhancement strategies include socialization, promotion, cooperation, fast drying equipment, training on weaving and packaging processes, as well as the use of technology, and scheduling of returned products. This study is expected to contribute to the development of the handicraft industry in Indonesia.